2018
DOI: 10.1111/jdv.15115
|View full text |Cite
|
Sign up to set email alerts
|

Photodermatoses in skin of colour

Abstract: Photodermatoses represent a heterogeneous collection of disorders unified by the characteristic of being provoked through exposure to ultraviolet radiation. Generally, these conditions are classified into the following categories: immunologically mediated photodermatoses, chemical- and drug-induced photosensitivity, photoaggravated dermatoses and photosensitivity associated with defective DNA repair mechanisms or chromosomal instabilities. The list of photodermatoses is extensive, and each individual photoderm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 87 publications
0
11
0
Order By: Relevance
“…Comprehensive reviews of data from photodiagnostic units in dermatology departments indicate that the photodermatoses most commonly seen are PLE, photoaggravated atopic dermatitis, actinic prurigo, chronic actinic dermatitis, solar urticaria and drug-induced photosensitivity. Photodermatoses occur in dark-skin populations, although with differing frequencies and characteristics from light-skin populations [ 158 ]. In a systematic review of population-based and dermatology outpatient studies of rosacea, a photoaggravated chronic inflammatory facial condition, a global prevalence of up to 5% was estimated; however, studies in which rosacea was self-reported yielded higher prevalence than in those where the condition was determined by examination [ 159 ].…”
Section: Harms Of Exposure To Uv Radiationmentioning
confidence: 99%
“…Comprehensive reviews of data from photodiagnostic units in dermatology departments indicate that the photodermatoses most commonly seen are PLE, photoaggravated atopic dermatitis, actinic prurigo, chronic actinic dermatitis, solar urticaria and drug-induced photosensitivity. Photodermatoses occur in dark-skin populations, although with differing frequencies and characteristics from light-skin populations [ 158 ]. In a systematic review of population-based and dermatology outpatient studies of rosacea, a photoaggravated chronic inflammatory facial condition, a global prevalence of up to 5% was estimated; however, studies in which rosacea was self-reported yielded higher prevalence than in those where the condition was determined by examination [ 159 ].…”
Section: Harms Of Exposure To Uv Radiationmentioning
confidence: 99%
“…Photodermatoses are generally classified into four categories: immunologicallymediated photodermatoses, chemical and drug-induced photosensitivity, photoexacerbated dermatoses, and genophotodermatoses. [1][2][3] Immunologically-mediated photodermatoses are further sub-divided into five diseases: polymorphous light eruption (PMLE), actinic prurigo (AP), chronic actinic dermatitis (CAD), solar urticaria (SU), and hydroa vacciniforme (HV). The pathophysiology of these diseases is still unclear, but it varies depending on different immune dysregulation.…”
Section: Introductionmentioning
confidence: 99%
“…An example of photodermatoses caused by endogenous agents is porphyrias, which are caused by an abnormal heme biosynthetic pathway. 1,3 Meanwhile, photoexacerbated dermatoses such as photoexacerbated eczema, photoexacerbated atopic dermatitis, systemic lupus erythematosus, autoimmune connective tissue diseases, vesiculobullous diseases, HIV photosensitivity, are the main groups of photodermatoses. 1 Last but not least, genophotodermatoses are rare genetic disorders that cause severe photosensitivity and other manifestations, and examples include xeroderma pigmentosum (XP), Bloom syndrome, and Rothmund-Thomson syndrome.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations